A study of clinical profile of pneumonia in Shivamogga institute of medical science attached hospital with special reference to curb scoring - P., Eshwarappa; R. A., Naveen Kumar; M., Ranganatha; G. K., Ranjith Kumar (International Journal of Advances in Medicine, 2021)
Background: Our study was done to study in detail the clinical profile of cases admitted with pneumonia to Mc Ganna hospital, SIMS, Shivamogga. Aim of the study were to study in detail the clinical profile of pneumonia and to know the morbidity and mortality associated with pneumonia by comparing with CURB score. Methods: Ours is a clinical, prospective, observational and open study. The study subjects were pneumonia patients admitted to Shivamogga institute of medical sciences attached McGann hospital, Shivamogga with signs and symptoms suggestive of pneumonia. After obtaining a detailed history and clinical examination the patients were subjected to relevant investigations. The complete data was collected in specially designed case recording form and transferred into a master chart which is then subjected to statistical analysis. Results: We studied 100 cases of pneumonia, out of which 12 patients presented with confusion, 30 patients presented with raised blood urea nitrogen, 28 patients with raised respiratory rate, and 30 patients with hypotension. CURB score of 0 was observed in 54 patients, score 1 in 16 patients, score 2 in 8 patients and score 3 in 22 patients. Prognosis was good in patients aged less than 50 years and those without any comorbidities. Fever was the most common symptom of presentation. Conclusions: Our study had highlighted the fact that CURB scoring is helpful in triaging pneumonia patients but it is not a good predictor of mortality in pneumonia patients.